2021
DOI: 10.2147/ccid.s337930
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Heparinoid Cream Containing Pseudo-Ceramide for Remission of Atopic Dermatitis

Abstract: Purpose: Atopic dermatitis (AD) is characterized by chronic inflammation, which frequently recurs, is exacerbated, and enters remission. A maintenance remission period is important for AD patients. We developed a formulation for use during AD remission, containing heparinoid and pseudo-ceramide that forms a lamellar structure. We evaluated the allergen permeability and examined the formulation's efficacy in maintaining remission in patients with AD. Materials and Methods: Seventeen AD patients applied a cream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It should be noted that coatings of formulations with lamellar structure also have a physical barrier function that suppresses allergen entry. 24 Interestingly, the improvement in SC function in the present study was most prominent in the participants with weak barrier function at the outset ( Figure 3A ). These participants experienced a significant decrease in the TEWL and an improved Cer [NP]/[NS] ratio, which is an indicator of epidermal turnover ( Figure 3C ).…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…It should be noted that coatings of formulations with lamellar structure also have a physical barrier function that suppresses allergen entry. 24 Interestingly, the improvement in SC function in the present study was most prominent in the participants with weak barrier function at the outset ( Figure 3A ). These participants experienced a significant decrease in the TEWL and an improved Cer [NP]/[NS] ratio, which is an indicator of epidermal turnover ( Figure 3C ).…”
Section: Discussionsupporting
confidence: 45%
“… 23 Furthermore, we found that a formulation containing synthetic pseudo-ceramides and a heparinoid that formed a lamellar structure after application and drying exhibited physical barrier function, effectively inhibiting allergen permeation. 24 Our assessment of the above-mentioned heparinoid formulation during AD remission revealed notable improvements in skin hydration and a reduction in the TEWL, accompanied by alleviation of itchiness. Taken together, these observations demonstrated that steroid and heparinoid formulations with a lamellar structure exhibit greater efficacy as therapeutic agents for AD than formulations without a lamellar structure.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Substances applied externally that penetrate the structure of the SC interact with its components. Substances containing compounds that physiologically occur in the SC, such as ceramides, cholesterol and its sulfate, and fatty acids affect the proportions of their counterparts resulting in supplementation of their deficiencies. Conversely, they may disrupt the natural quantitative balance of lipid components to induce an increase in skin permeability. It has been found that changes in the composition and chain length of fatty acids present in their free forms as well as bound to SC ceramides change their melting point and membrane permeability .…”
Section: Natural Components Of the Sc Are Compounds That Regulate The...mentioning
confidence: 99%
“…A cream containing heparinoid and P-Cer forms lamellar structures that result in inhibiting allergen penetration with an improvement in SC functions. This cream is effective in maintaining the AD remission period [ 91 ]. The cream with steroids and P-Cer, which also forms a lamellar structure, not only demonstrates anti-inflammatory effects but also significantly improves SC functions [ 88 ].…”
Section: Discussionmentioning
confidence: 99%